The Pinchuk example revisited - Fernandes, Filipe; Jelonek, Zbigniew (Comptes Rendus. Mathématique)
In this note we provide two special counterexamples to the strong real Jacobian Conjecture; the first one is surjective, the second one has non-dense image.